Game Edukasi berbasis Android: Urgensi Penggunaan, Pengembangan dan Penguji Kelayakan - Kurnia Muhajarah; Farida Rachmawati (Unversitas Muhammadiyah Mataram, 2019)
Abstract: The development of information technology today has been able to package the conditions and realities of learning to be more attractive. Educational games are games or fun activities that contain educational content and their use, which is a necessity. This research is a library research. The data was extracted and analyzed in depth using the qualitative theory of Bogdan and Cresswell. The results showed that the ability to absorb each student in learning was strongly influenced by the learning experience, mode, modality and learning style.There are differences regarding this matter, it can be accommodated by the use of educational games as learning media. The use of educational games does not conflict with behaviorism and cognitivism theories. On the other hand, the use of android-based educational games serves to make it easier forstudents to operate and use them. However, because of its simplicity, the use of educational games must be tested first through strict instruments by experts to be able to meet the marketing standards, test content and maximize its use.Abstrak: Perkembangan teknologi informasi dewasa ini telah mampu mengemas kondisi dan realitas pembelajaran menjadi lebih menarik. Game edukasi merupakan permainan atau aktivitas menyenangkan yang memuat konten pendidikan dan penggunaanya, merupakan sebuah keniscayaan Penelitian ini merupakan penelitian kepustakaan. Data digali dan dianalisis secara mendalam menggunakanteori kualitatifnya Bogdan dan Cresswell. Hasil penelitian menunjukkan bahwa kemampuan daya serap masing-masing peserta didik dalam pembelajaran sangat dipengaruhi oleh pengalaman belajar, modus, modalitas dan gaya belajarnya.Adanya perbedaan mengenai akan hal ini, bisa diakomodir dengan penggunaan game edukasi sebagai media pembelajaran. Penggunaan game edukasi ini tidak bertentangan dengan teori behaviorime dan kogntivisme. Di lain sisi, penggunaan game edukasi berbasis android, berfungsi untuk memudahkan peserta didik dalam pengoperasian dan penggunaannya. Namun demikian, karena kemudahannya, penggunaan game edukasi harus diujilayakkan dahulu melalui instrumen yang ketat oleh para ahli untuk dapat memenuhi standar edar, uji konten dan memaksimalisasi pemanfaatannya.